(untitled) (Revista de Ciências Agroveterinárias, 2013)
In two top sequences in the Southern Plateau of Santa Catarina, we studied the chemical, physical and morphological characteristics of seven soil profiles from effusive rocks (basalts and rhyodacites) of the Serra Geral formation. The physical characterization consisted of determining the texture, water dispersible clay and degree of flocculation. The chemical analysis consisted of determining the pH in H2O and KCl, Ca2+, Mg2+, K+, Na+, Al3+, H+Al and organic carbon (OC). Also studied was the contribution of clay and organic carbon in Cation Exchange Capacity (CEC) by the graphic method of Bennema. The soils originated from rhyodacites were classified as Cambissolos Háplicos (Haplumbrept), and developed from basalt as Nitossolos Vermelhos (Kandiudox). The Haplumbrept have a strong reaction to acid, very high levels of exchangeable Al and low values of sum and base saturation, possessing alito or alumina characteristics, whereas the Kandiudox have a less acidic reaction, lower levels of exchangeable Al, and values sum (SB) and base saturation (V%) higher than in Haplumbrept, and dystrophic. The estimate of the contribution of clay and organic carbon in the Cation Exchange Capacity (CEC) using the Bennema method resulted in values of the activity of clay (T) lower than those obtained by the method recommended by the Brazilian System of Soil Classifi cation (SiBCS). The contribution of CO in the CTC is relevant in soils of regions with higher altitudes, because the organic matter levels are high even in the subsurface layers. Therefore, it is suggested to consider the effect of organic matter in the calculation of the activity of clay, especially in soils with higher altitudes, due to its importance in the framework of the soil in the third categorical level.